Secondary Torsion of Vermiform Appendix with Mucinous Cystadenoma - Maki Kitagawa (Case Reports in Gastroenterology, 2007)
Torsion of the vermiform appendix is a rare disorder, which causes abdominal symptoms indistinguishable from acute appendicitis. We report a case (a 34-year-old male) of secondary torsion of the vermiform appendix with mucinous cystadenoma. This case was characterized by mild inflammatory responses, pentazocine-resistant abdominal pain, and appendiceal tumor, which was not enhanced by the contrast medium on computed tomography presumably because of reduced blood flow by the torsion. These findings may be helpful for the preoperative diagnosis of secondary appendiceal torsion.